2020
DOI: 10.1177/1468798420925116
|View full text |Cite
|
Sign up to set email alerts
|

Young children’s digital literacy practices in the sociocultural contexts of their homes

Abstract: This socioculturally framed case study investigates the digital literacy practices of two young children in their homes in Finland. The aim is to generate new knowledge about children’s digital literacy practices embedded in their family lives and to consider how these practices relate to their emergent literacy learning opportunities. The study asks two questions, ‘How do digital technologies and media inform the daily lives of children in their homes? Moreover, how do the sociocultural contexts of homes medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 41 publications
0
36
0
1
Order By: Relevance
“…Thus, teachers should have also developed digital-literacy-based teaching materials. Studies by Alfia et al (2020), Duriawati et al (2020), Fernanda et al (2020, Kumpulainen et al (2020), andPradana et al (2020) showed that digital literacy could support the needs of 21 st -century learners to compete in a global world.…”
Section: The Learners' Expectation Toward the Developed Teaching Materialsmentioning
confidence: 99%
“…Thus, teachers should have also developed digital-literacy-based teaching materials. Studies by Alfia et al (2020), Duriawati et al (2020), Fernanda et al (2020, Kumpulainen et al (2020), andPradana et al (2020) showed that digital literacy could support the needs of 21 st -century learners to compete in a global world.…”
Section: The Learners' Expectation Toward the Developed Teaching Materialsmentioning
confidence: 99%
“…Parents also support the use of appropriate digital devices for early childhood (Kumpulainen et al, 2020;Mikelić Preradović et al, 2016). In particular, even parents have positive attitudes towards children's computer use and believe that children should acquire technical skills and should be taught how to use computers to promote academic development and future opportunities (Hatzigianni & Margetts, 2014).…”
Section: Effect Of Parental Involvement (A) On Child Independence (Y) In a Pandemic Situationmentioning
confidence: 99%
“…Fostering digital literacy skills is crucial for ensuring digital inclusion and resolving inequities related to the digital divide [3]. Digital inclusion refers to mending the digital divide in terms of enhancing equitable access to digital devices and the internet so that individuals can meaningfully participate in all sectors of a knowledge-and information-driven society [3,4]. Considering North America's information and data-powered infrastructure, digital literacy skills are, and will continue to be, a crucial component of full and informed participation within evolving educational, civic, corporate, social, and economic spaces [5][6][7].…”
Section: Introductionmentioning
confidence: 99%